(untitled) (Teacher Half-Yearly Journal, 2025)
This is the age of information communication and technology. It has controlled everyday’s work of people. Without it, people now-a-day feel themselves completely isolated. From the very beginning of the day, people use it as the mainstay of their daily affairs. This study investigates the utilization of ICT tools in educational settings focusing on the ICT resources commonly employed for classroom teaching and to explore the challenges faced by both teachers and students. It has used the descriptive survey research design to outline the overall strategy and procedures for data collection and analysis consisting of 83 students and 25 teachers as the sample and observation notes and open-ended questions as the tools. The study concludes that teachers require adequate training, resources, and support to successfully implement ICT-based instruction and become more capable, professional educators, equipped to address the global challenges of teaching ICT in modern classrooms. For teacher education programs to effectively prepare educators for the demands of the 21st century, they must prioritize competitiveness, competence, and skill development, with ICT playing a central role.